Zinc response of maize (Zea mays L.) grown on sandy inceptisols in Western Nigeria - Osiname, O.; Kang, B.T.; Schulte, E.E.; Corey, R.B. (Wiley, 1973)
Field experiments were conducted with IITA maize (Zea mays L.) composite B at six locations ranging from forest to savannah in the Western State of Nigeria to assess the level of zinc response on sandy Inceptisols. Zinc, as Na2 Zn EDTA, was applied as broadcast application at 0, 1.0, 2.0, 4.0, and 8.0 kg/ha. Zinc response in terms of growth development and grain yield was limited to the savannah where yield increases of 1,747 kg/ha of grain were obtained with application of Zn at 1 to 2 kg/ha. For optimum grain yield, 12 ppm Zn in tissue appeared minimal. Maize response to Zn application was most probable when the 0.1N HCl soil-extractable Zn was less than 1.0 ppm when measured at silking time.